Үхлийн тухай ойлголтоос ойролцоо утгын онцлогийн тухай (МНТ-ны герман орчуулгын жишээгээр): Special Features of the Synonymously used Words and Idiomatic Expressions about Dying and Death - G., Erdenenaran (Mongolian Journal of Foreign Languages and Cultures, 2023)
The lifestyle of nation, which developed into a definite form in the course of history, fades into the language. Eventually, the language itself becomes the tools to describe the phenomena in the universe in their own specific society, history, religion and culture to create appropriate judgement, and describe them with their language. Therefore, language unit which is the method, mode of describing with a language is the term or the synonyms at the level of stylistics in the vocabulary.